2015
DOI: 10.1007/s13277-015-4399-6
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative effect of BI-69A11 and celecoxib enhances radiosensitization by modulating DNA damage repair in colon carcinoma

Abstract: Amplification of PI3K-Akt pathway promotes radioresistance in various cancers including colorectal carcinoma. Local recurrence in colon cancer causes poor prognosis affecting overall survival of cancer-affected patient population. To avoid local recurrence, pre-operative or post-operative additional radiotherapy is given. However, main concern regarding radiotherapy is to increase the radiosensitivity of malignant cell without hampering the activities of normal cells. In this context, addition of two or more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…The G2 arrest in tumor cells provides time for the repair processes to operate which are critical for ensuring cell survival after DNA damage (41). It was suggested that the combination of BI-69A11 and celecoxib impaired IR-induced DSB repair, attenuated the G2/M cell cycle and then enhanced the radiosensitivity of CRC cancer cells (42). In the present study, CCL244 cells with irradiation revealed prolonged G2/M phase arrest.…”
Section: Discussionmentioning
confidence: 45%
“…The G2 arrest in tumor cells provides time for the repair processes to operate which are critical for ensuring cell survival after DNA damage (41). It was suggested that the combination of BI-69A11 and celecoxib impaired IR-induced DSB repair, attenuated the G2/M cell cycle and then enhanced the radiosensitivity of CRC cancer cells (42). In the present study, CCL244 cells with irradiation revealed prolonged G2/M phase arrest.…”
Section: Discussionmentioning
confidence: 45%
“…The in vitro anticancer activity was measured by using the 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide (MTT; a yellow tetrazole) assay in HeLa cells. Different concentrations of CBL, 5 , and 6 were added to the wells and subjected to photolysis.…”
Section: Methodsmentioning
confidence: 99%
“…Radioresistance can be regulated by a series of pathways, including DNA damage repair 2 , telomere maintenance 3 , cell cycle progression 4 , cell apoptosis 5 , and cell proliferation 6 . Some reports have shown that the ubiquitin/proteasome system (UPS) participates in the regulation of these pathways 7 .…”
Section: Introductionmentioning
confidence: 99%